The Impact of Meaningful Work on Employees:A Systematic Literature Review - Pertiwi, Talitha Lintang; Prihastuty, Rahmawati; Febriyanti, Safiah; Filhal, Najwa Haq; Rahmiatun, Tri Wahyuni Oktami (Universitas Paramadina, 2025)
Meaningful work refers to the extent to which individuals perceive their jobs as valuable, impactful, and aligned with their life purpose. This concept has gained increasing importance in the modern workplace, as it has been shown to contribute to both employee well-being and organizational effectiveness. This study aims to examine the impact of meaningful work experienced by employees using a systematic literature review method, with research findings sourced from credible academic articles identified through the software Publish or Perish version 8 and selected using Rayyan.id. The inclusion criteria for reviewed articles were: publications between 2016 and 2025, written in Indonesian, employing a quantitative research design, and focused on employees in Indonesian companies. After a thorough selection process, the study revealed that meaningful work has a significant positive influence on several key aspects of work life, including organizational commitment, job stress levels, employee loyalty, creativity, and work engagement. Meaningful work not only enhances individual psychological well-being but also plays a strategic role in supporting overall organizational performance.